Efficiency, stability and asset quality of Islamic vis-à-vis conventional banks: evidence from Indonesia - Sakti, Muhammad Rizky Prima; Mohamad, Azhar (Emerald Group Publishing Ltd., 2018)
urpose – This paper aims to examine how Indonesian Islamic banks differ from conventional banks in terms of their business model, asset quality, stability and efficiency. Design/methodology/approach – Based on data from 2008 to 2012, the authors use t-test, z-score and data envelopment analysis (DEA) to assess the business model, as well as the asset quality, stability and efficiency of both the Islamic and conventional banks. Findings – The results indicate that there are significant differences between the two – Islamic banks appear to not follow the conventional business model. Secondly, Islamic banks seem to have better asset quality and to be more stable than their conventional counterparts. Originality/value – Finally, the DEA results also indicate that Islamic banks are relatively more efficient than conventional banks, as shown by their higher overall efficiency, as well as technical efficiency.